Psychometric properties of the Patient Health Questionnaire (PHQ-9) in medical students, Lima, Peru. - Huarcaya-Victoria, Jeff (2020)
The Patient Health Questionnaire (PHQ-9) is recognized as a psychometrically valid and reliable intrument; however, when assessed by means of a factor analysis method, it remains unclear whether a one- or two-factor structure is the best. Objective: To evaluate the psychometric properties and the factor structure of the PHQ-9 in medical students of a university in Peru. Material and Methods: Instrumental study in 200 medical students. An exploratory factor analysis (EFA) was performed to evaluate the internal structure of the PHQ-9, followed by a confirmatory factor analysis (CFA) of three models. Results: An adequate internal consistency was found (Cronbach’s alpha = 0,903).Through the CFA, the bifactorial model (x2 (17) = 26,451, p = 0,067; CFI = 0,991; GFI = 0,969; RMSEA = 0,056) had a better adjustment than the unidimensional and bi-dimensional factor models. Conclusion: The PHQ-9 is an instrument with adequate psychometric properties for its application among medical students of a Peruvian university. The CFA revealed that a bifactorial model, in which both the general factor and latent somatic and cognitive/affective factors are taken into account, yields more fitting results.